2004
DOI: 10.1111/j.0022-202x.2004.22520.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model System Using Tape Stripping for Characterization of Langerhans Cell-Precursors In Vivo

Abstract: Little is known about the immigration of bone marrow-derived progenitors of Langerhans cells (LC) into the epidermis. We developed an in vivo system based on the tape stripping method that allowed us to study the immigration of LC into the epidermis after intradermal injection of bone marrow-derived dendritic cells (DC). Tape stripping induced a mechanical disruption of the epidermal barrier that led to skin inflammation and subsequent emigration of LC and dermal DC from the skin. Emigrating LC and dermal DC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
63
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 45 publications
9
63
1
Order By: Relevance
“…We did not use tape stripping, which may disturb the integrity of the epidermis (20). Even without the addition of adjuvants, application of cream under an occlusive bandage caused m-LCs to up-regulate both CD80 and CD86, producing a bimodal CD80/ 86 profile as m-LCs first reached the dLN 48 h after immunization ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We did not use tape stripping, which may disturb the integrity of the epidermis (20). Even without the addition of adjuvants, application of cream under an occlusive bandage caused m-LCs to up-regulate both CD80 and CD86, producing a bimodal CD80/ 86 profile as m-LCs first reached the dLN 48 h after immunization ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Disturbing the skin barrier by tape stripping (7), or by simultaneous application of cholera toxin (6) or TLR ligands such as CpG oligonucleotides (6) or imiquimod (25) have all been shown to provide an adjuvant effect. We chose to use skin barrier disruption because this method might be applicable in clinical trials, and because we had observed that it effectively induced migration of LC from the skin to the draining lymph nodes (26). Throughout our study, we compared groups of mice that received OVA on untreated or on tape-stripped skin.…”
Section: Discussionmentioning
confidence: 99%
“…8A). It has been reported that LCs can be replaced from precursors that originate in the blood, such as those of monocyte origin (17,28). In addition, LC precursors also exist within the skin itself (15).…”
Section: On Resolution Of Infection Lc Replacement In the Reformed Ementioning
confidence: 99%